PERSEPSI MASYARAKAT TERHADAP PUSPA, SALAM DAN GAYAM SEBAGAI TANAMAN INTI RESTORASI TAMAN NASIONAL GUNUNG MERAPI - , ULYA AFIDA IANATI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Perception is a process to make a sense of stimulus input captured by human sense to search for the interpretation based on knowledge and experience (Passer and Smith, 2008). Restoration in Merapi Mountain National Park is purposed to return a degraded or former ecosystem that resemble as close as possible its pre-disturbed state caused by Mt. Merapiâs eruption in 2010, both its structure and function. Restoration activities were started by establishing restoration plot planted with several species such as puspa, salam and gayam. This study is aimed to know their perception about recognizing and utilizing those species. The perceptions of the three species are expected to be an important source of information and material consideration in purpose to restoration management activities through those third species in TNGM. The study was conducted in two Padukuhan around Kali Kuning, namely Padukuhan Gondang and Pangukrejo. Respondents that were drawn in this study was quantified and stratified by household heads (Kepala Keluarga/KK). The number of respondents interviewed randomly was measured from 50% of the total number of household heads (KK) in every Padukuhan. The reserach used interview technique using questionnaires as a guidance and conducting observation activities. Description of the perception on puspa, salam and gayam and their utilization are presented in graphical form. Based on the results, the study shows that there are perceptionâs differences and similarities about recognizing and utilizing puspa, salam and gayam as core restoration plants in TNGM. The perceptions are influenced by several things. They are the differences in the location of the two Padukuhan, the existence of those species either trees or seedlings, the utilization in daily life, the respondents involvement in treating plant plots, the difference of their occupation, their gender and age. Based on their perception, puspa, salam and gayam have their own benefit as protection functions and specific benefit. Puspa is utilized for crafts, medicine and fertilizer. Salam is useful for seasoning and medicine. Gayam is able to be used for food.